2020
DOI: 10.1002/cncr.32972
|View full text |Cite
|
Sign up to set email alerts
|

NPC‐0501 trial on the value of changing chemoradiotherapy sequence, replacing 5‐fluorouracil with capecitabine, and altering fractionation for patients with advanced nasopharyngeal carcinoma

Abstract: BACKGROUND: A current recommendation for the treatment of patients with locoregionally advanced nasopharyngeal carcinoma (NPC) is conventional fractionated radiotherapy (RT) with concurrent cisplatin followed by adjuvant cisplatin and 5-fluorouracil (PF). This randomized NPC-0501 trial evaluated the therapeutic effect of changing to an induction-concurrent sequence or acceleratedfractionation sequence, and/or replacing 5-fluorouracil with capecitabine (X). METHODS: Patients with American Joint Committee on Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Several studies and meta‐analyses have corroborated the results described by Lee et al 1 In the era of intensity‐modulated radiotherapy, a survival benefit was described in randomized clinical trials exploring the added value of induction cisplatin–based chemotherapy with either 5‐FU and docetaxel (the TPF regimen; hazard ratio for failure, 0.68) 8,12 or gemcitabine (stratified hazard ratio for death, 0.43) 7 . Apart from NPC‐0501, no direct comparisons between induction schedules have been published so far.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Several studies and meta‐analyses have corroborated the results described by Lee et al 1 In the era of intensity‐modulated radiotherapy, a survival benefit was described in randomized clinical trials exploring the added value of induction cisplatin–based chemotherapy with either 5‐FU and docetaxel (the TPF regimen; hazard ratio for failure, 0.68) 8,12 or gemcitabine (stratified hazard ratio for death, 0.43) 7 . Apart from NPC‐0501, no direct comparisons between induction schedules have been published so far.…”
supporting
confidence: 77%
“…We congratulate Lee et al for their great efforts in conducting such an ambitious and complex randomized clinical trial, 1 and we are grateful for their sharing with the scientific community the updated results of their work formerly published by Cancer in 2015 2 …”
mentioning
confidence: 97%
See 1 more Smart Citation
“…65 Long-term data from a multicentre, randomised, factorial trial showed that shifting from the concurrent-adjuvant to the induction-concurrent sequence achieved significant improvements in PFS and marginal improvements in OS without an adverse impact on late toxicity [II, B]. 66 The selection of patients to receive more ChT or immunotherapy in addition to CRT in the form of either ICT or AC is a therapeutic area that is being explored in ongoing randomised controlled trials (see below for individualised risk assessment).…”
Section: Management Of Local/locoregional Diseasementioning
confidence: 99%
“…In the current issue of Cancer , Lee et al 18 attempt to answer the aforementioned question and report a very complex, 6‐arm randomized trial comparing chemotherapy sequencing, types of chemotherapy, and radiation fractionation schedules. The authors are to be congratulated for conducting and completing this large multicenter trial.…”
mentioning
confidence: 99%